Physiological, neuromuscular, and perceptual responses to matched high-intensity intermittent exercise in soccer players under fed and ramadan-type fasting conditions - Ates, O.; Ulupinar, S.; Kaya, K.; Tortu, E.; Türksoy Isim, A.; Kesler, A.; Ince, I.; Gençoglu, C.; Çabuk, S.; Demirli, A.; Özbay, S. (International Journal of Sport Nutrition and Exercise Metabolism, 2026)
Ramadan-type diurnal fasting, which restricts both food and fluid intake from dawn to sunset, may influence physiological, metabolic, and perceptual responses during high-intensity exercise. However, its acute effects under matched external workload conditions in field-based soccer training remain unclear. This study examined the physiological, neuromuscular, metabolic, and perceptual responses to a matched high-intensity intermittent training session performed under fed and Ramadan-type fasting conditions. Twenty male university-level soccer players completed two counterbalanced sessions. External load was matched using 10-Hz GPS monitoring. Physiological variables, including oxygen uptake, carbon dioxide production, respiratory exchange ratio, minute ventilation, and heart rate, along with blood lactate concentration, session rating of perceived exertion, perceptual scales (thermal discomfort and thirst), neuromuscular performance assessed via countermovement jump height and power, and body mass were measured before and after exercise. External mechanical load did not differ between conditions. Ramadan-type fasting elicited significantly higher minute ventilation, mean and maximal heart rate, and session rating of perceived exertion, whereas carbon dioxide production, respiratory exchange ratio, and peak blood lactate concentration were significantly lower. Oxygen uptake did not differ between conditions. Thermal discomfort and thirst increased from pre- to postexercise in both trials (time effect), with perceived thirst showing a greater increase under fasting conditions (interaction effect). Countermovement jump height and power demonstrated significant pre-to-post reductions (time effect) without condition or interaction effects. Body mass decreased significantly from pre- to postexercise in both trials (time effect), with no condition or interaction effects. These findings indicate that Ramadan-type fasting increases internal physiological and perceptual load during high-intensity intermittent soccer training despite identical external workloads, while neuromuscular performance and exercise-induced body mass loss remain preserved. Practitioners should consider that athletes may experience higher internal strain during fasting-based sessions even when mechanical output is maintained.